Residents' Perceptions Of Religious Tourism And Its Socio-Economic Impacts In Brgy. Pomponan, Baybay City, Leyte - Palma Balaga, Cle Marven; Salado Maravilla, Vicente (Institut Pariwisata dan Bisnis Internasional, 2024)
Religious tourism consists of pilgrimages, visiting holy sites and sacred structures, and travel for worship and devotion. Several studies have investigated the concept of religion and tourism, but relatively few have examined how the residents in the community view religious tourism and its effects on sacred sites. This research aims to determine the residents' perceptions of religious tourism and its socio-economic impacts in Brgy. Pomponan, Baybay City, Leyte in their church houses the Miraculous Image of Saint Antonio de Padua S.urvey questionnaires were distributed to 250 residents. Majority of the residents had a favorable view and perception of religious tourism and the presence of religious tourists and pilgrims in their community. Residents were appreciative of the positive impact that religious tourism had on their economy, with transportation and public utility infrastructure being the most significant. Furthermore, they praised the religious tourists' respect and appreciation for local customs and traditions, attributing it to the rich cultural exchange that led to the preservation of their traditions. The paper suggests management and development strategies to address the issues of traffic, congestion, and pollution caused by religious tourists, particularly during feast days and special events.